Epidemiology of Carbapenemase-Producing Klebsiella pneumoniae in a Portuguese Tertiary Hospital. (30th September 2020) - Peres, D; Pereira-Rocha, N; Alves, C; Correia, S
Abstract: Background: Carbapenemase-producing Klebsiella pneumoniae (CPKp) are considered a public health problem. To manage this multidrug-resistant organism (MDRO), it is important to identify individuals at higher risk. We describe risk factors for CPKp among a population who acquired this MDRO, in a tertiary hospital Center (THC), from 2017 to 2019. Methods: Descriptive study, with data from medical record, in a 1100 bed THC, with active surveillance (high risk population at admission and CPKp direct contacts). Participants: patients > =18 years old, with length of stay (LOS) >48 hours, in which CPKp was identified in clinical samples > =48 h after admission and without previous history of this MDRO. Results: Incidence rate increased from 0.031 (2017) to 0.090 (2018) cases per 1000 patient-days and was 0.081 in 2019 (p = 0.004). Evolution of CPKp proportion was 1.6%, 3.9% and 4.1%, respectively. In 2019, 12 patients (40.0%) were at intensive care when this MDRO was detected. During these 3 years, CPKp was more frequently identified in urine (31.3 - 54.5%) and respiratory products (13.3 - 36.4%). The median LOS until CPKp isolation was 10.0 to 24.0 days and, until discharge, 15.0 to 25.5 days. Fatal outcome occurred in 8 (25.0%) and 7 (23.3%) patients in 2018 and 2019, respectively. Most cases were exposed to antibiotics (81.8 - 90.6%), had a urinary catheter (63.6 - 75.0%) and were dependent for hygiene activities (63.6 - 66.7%). Many had a central line (21.9 - 43.3%), previous surgery (45.5 - 63.3%) and hospital admission in the previous 6 months (27.3 - 40.6%). Along these 3 years, none of these variations was statistically significant. Conclusions: In this THC, CPKp increased from 2017 to 2018 and remained stable afterwards. It affected mostly male patients, exposed to antibiotics, with urinary catheter and dependent in their hygiene activities. In order to have an adequate CPKp containment strategy it is essential to know the population who acquired this MDRO. Key messages: CPKp increased from 2017 to 2018 and remained stable afterwards, affecting mostly male patients, exposed to antibiotics, with urinary catheter and dependent in their hygiene activities. In order to have an adequate CPKp containment strategy it is essential to know the population who acquired this MDRO during their stay.